(untitled) (Research, Society and Development, 2023)
Currently, 700,000 people die each year due to infections with multidrug-resistant microorganisms and this number is expected to increase to ten million deaths per year by 2050. In this context, the search for new antimicrobial compounds derived from medicinal plants, more effective and accessible, as an alternative therapy for bacterial or fungal treatment is of paramount importance. The aim of this review is to provide an extensive summary of the in vitro antibacterial and antifungal properties of the medicinal plant jatobá (Hymenea courbaril L.) commonly used in the Brazilian Cerrado biome to treat infections. In addition, document information about the evaluated plant parts, the type of extract, methods, microorganisms and secondary metabolites used for the species. A systematic literature search was performed using electronic databases PubMed, Scielo, Google Scholar, EBSCO, and Bireme, from 2010 to date. Of the 47 titles identified by the search, 20 were suitable according to the inclusion and exclusion criteria. The results showed that the most used part of the plant was the bark (50%), followed by the leaves (17%). Certain compounds such as fisetin, fisetinediol, α-cadinol, caryophyllene oxide, spathulenol and taxifolin, isolated from H. courbaril L., have been shown to be active and should be further studied in order to develop effective drugs against bacteria and fungi. It is concluded that this review will be useful for future studies, as it provides useful information for the selection of clinically important jatobá extracts and their potential antifungal and antibacterial properties.